Physical and Sensory Characteristics of Mayonnaise Using Functional Ingredients of Galo-galo Honey (Tetrigona apicallis) - Novia, Deni; Walfadillah , Reren; Sandra, Afriani (Faculty of Animal Science, Universitas Brawijaya, 2024)
Mayonnaise results from an emulsion of vegetable oil in acid stabilized by lecithin (egg yolk). As one of the main components, acetic acid is a synthetic material that has side effects if it is consumed at high levels and over a long period. An effective natural acidifying ingredient, as a substitute for vinegar, is the galo-galo honey of the Tetrigona apical species, which has a low pH of 2.70. It has high organic acid content, gluconic acid content, and high antioxidant, antimicrobial, flavonoid, and phenolic contents. This study aimed to determine the effect of adding galo-galo honey on the physical and sensory properties of mayonnaise. This study used an experimental method with a completely randomized design, five treatments, and four replications. The treatments given were the percentage of galo-galo honey as much as A (0%), B (0.5%), C (1.5%), D (2.5%), and E (3.5%) of the weight of the oil. This study revealed that using gallo-galo honey during mayonnaise affected the moisture content, viscosity, and sensory characteristics but did not influence emulsion stability. The use of 3.5% galo-galo honey for mayonnaise is the best treatment with average values, namely, a moisture content of 20.03%, viscosity of 2347 cP, and emulsion stability of 100%, and the sensory test results were rather similar to aroma, texture, color, taste, and overall acceptability. The addition of galo-galo honey, which comes from stingless bees native to West Sumatra as a functional ingredient, will produce mayonnaise, which has benefits for the body's health.